The applied improvisation mindset : tools for transforming organizations and communities - Dudeck, Theresa; McClure, Caitlin (London, England : Zed Books, 2021)
"How can the practice of improvisation become the lens through which we view the world? The Applied Improvisation Mindset takes readers deep into the maturing field of Applied Improvisation (AI), with stories of 18 practitioners from five countries who embrace an improvisation mindset to create a more collaborative, equitable, sustainable, and joyous world. Myriad organizations have discovered how the mindset and skills applied by great improvisers onstage can reveal emergent, generative ways of interacting with others offstage. With case studies on developing presentation skills, reducing anxiety in teens, or preparing climate risk managers across the globe for the challenges ahead, this second volume serves as a valuable resource for both experienced and new AI facilitators. It is a primer for higher education and K-12 faculty combatting traditional teaching limitations and a practical ?how to? for theatre practitioners, artists, educators, or anyone seeking to transform their organizations and communities."--
List of Figures List of Tables Acknowledgments -- Introduction -- Theresa Robbins Dudeck and Caitlin McClure -- PART ONE: Developing the Leaders We Need -- 1.Improv is the Gym: Presentation Skills and Beyond at H4B's Catapult College -Kat Koppett (arts practitioner, USA) -- 2.The Business School Collaboration Lab: Turning Leader Development Into a Rigorous Experiment in Creative Collaboration - Pamela Burke (Stevens Institute of Technology and Columbia University Teachers College, USA) 3.Developing Strategic, Action Oriented, and Mindful Leaders - Petro Janse van Vuuren (University of the Witwatersrand School of Arts, Johannesburg, South Africa) -- PART TWO: Developing the Youth We Need 4.The Improv Project's Detroit Yes, And - Peter Felsman (Stony Brook University, USA) and Tiger Veenstra (arts practitioner, USA) 5.Spontaneity in Culturally Sustaining Pedagogy: Valuing the ?In-between? and ?After? of Applied Improvisation - -- Moriah Flagler (The Ohio State University, USA) 6.Of Course We Improvise! What the Best Teachers Do (and how they do it) - Nick Sorensen (founder of The Improvising School, UK) -- PART THREE: Developing the Communities We Need 7.Trips to No-Mistakes-Land: Improvisation as a Meta-Skill for Doctoral Students - Gunter Lösel (Zurich University of the Arts, Switzerland) 8.Transforming the Culture of Communication in Systems Biology at Harvard Medical School - Raquell Holmes (arts practitioner, USA) and Mia Anderson (arts practitioner, USA) 9.Playing Around with Changing the World - Carrie Lobman (Rutgers University, USA) and Marian Rich (arts practitioner, USA) 10.The Joy of Dementia - Mary Fridley (East Side Institute, NYC, USA) and Susan Massad (East Side Institute, USA) 11.A Funny Thing Happened on the Way to Disaster: Reimagining Learning for the Humanitarian Sector -- Barbara Tint (Portland State University, USA) and Bettina Koelle (arts practitioner, South Africa) -- Appendices A. Key Improvisation Tenets and Terms B. About the Workbook and List of Exercises.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Improvisation (Acting); Employees -- Training of; Creative ability in business; Acting techniques; Electronic books